2016
DOI: 10.1007/s12046-016-0482-y
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of local and global features for classification of abnormality in mammograms

Abstract: Mammography is the most widely used tool for the early detection of breast cancer. Computerbased algorithms can be developed to improve diagnostic information in mammograms and assist the radiologist to improve diagnostic accuracy. In this paper, we propose a novel computer aided technique to classify abnormalities in mammograms using fusion of local and global features. The objective of this work is to test the effectiveness of combined use of local and global features in detecting abnormalities in mammograms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 14 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…The parameters of SVM, such as gamma and soft margin constant, are optimized by iteratively conducting cross-validation within the training data. In cases where the datasets are not linearly separable in the original finitedimensional space, the data can be re-mapped into a sufficiently higher-dimensional space using a defined kernel function, kðx; yÞ, which presumably ensures an easier separation of the datasets [35]. The hyperplane defined in the higher-dimensional space can be viewed as a non-linear separating hyperplane in the original finite-dimensional space.…”
Section: Classification Of Eeg Signals With Svmmentioning
confidence: 99%
“…The parameters of SVM, such as gamma and soft margin constant, are optimized by iteratively conducting cross-validation within the training data. In cases where the datasets are not linearly separable in the original finitedimensional space, the data can be re-mapped into a sufficiently higher-dimensional space using a defined kernel function, kðx; yÞ, which presumably ensures an easier separation of the datasets [35]. The hyperplane defined in the higher-dimensional space can be viewed as a non-linear separating hyperplane in the original finite-dimensional space.…”
Section: Classification Of Eeg Signals With Svmmentioning
confidence: 99%
“…In the feature extraction step, some statistical features were extracted and Finally, the proposed CAD system has been compared with other papers in the field that have the same conditions to prove the efficiency of the proposed method as shown in Table 11. Regarding the MIAS dataset, it was clear that the results have shown that the proposed CAD system recorded the highest accuracy and AUC compared to El-Toukhy et al [47], Beura et al [15], Pawar and Talbar [16], Phadke and Rege [48], and Mohanty et. al.…”
Section: Discussionmentioning
confidence: 90%
“…The classification performance of the introduced system is further assessed in comparison to a number of state-of-the-art breast cancer detection systems as reported in Table 4. The early studies [72][73][74][75][76][77][78] focused mostly on identifying the textural features of breast tissues and applying traditional machine learning algorithms for classification purpose. The outcomes of those methods were not appropriated for the accurate classification of breast lesions since they lack high accuracy and sensitivity.…”
Section: Comparing the Performance And Conclusionmentioning
confidence: 99%